Conditional Lethal Mutants of Adenovirus 2-Simian Virus 40 Hybrids I. Host Range Mutants of Ad2(+)ND1 - Grodzicker, Terri (1974)
Human adenovirus type 2 (Ad2) grows poorly in monkey cells, although this defect can be overcome by co-infection with simian virus 40 (SV40). The nondefective Ad2-SV40 hybrid virus, Ad2(+)ND1, replicates efficiently in both human and African green monkey kidney cells, presumably due to the insertion of SV40 sequences into the Ad2 DNA. Several mutants of Ad2(+)ND1 have been isolated that grow and plaque poorly in monkey cells, although they retain the ability to replicate and plaque efficiently in HeLa cells. One of these mutants (H39) has been examined in detail. Studies comparing the DNA of the mutant with Ad2(+)ND1 either by the cleavage patterns produced by Escherichia coli R·RI restriction endonuclease digestion or by heteroduplexing reveal no differences. The pattern of protein synthesis of Ad2(+)ND1 and H39 in monkey cells is quite different with the mutant resembling Ad2, which is defective in the synthesis of late proteins. However, in human cells, the proteins synthesized by H39 and the parent Ad2(+)ND1 are very similar. The production of SV40 U antigen in H39-infected cells is different from that in Ad2(+)ND1-infected cells. Finally, the growth of H39 in monkey cells can be complemented by SV40.